Virulence and Diversity of Blumeria graminis f. sp. hordei in Israel and in the Czech Republic - Dreiseitl, Antonín; Dinoor, Amos; Kosman, Evsey (Plant disease, 2006)
Three hundred and nine isolates were obtained from three natural populations of Blumeria graminis f. sp. hordei occurring on wild barley (Hordeum vulgare subsp. spontaneum) at two locations in Israel during 1997 and 1999. Their virulence frequency was determined on 32 differential lines. No isolate was virulent on the differential lines possessing the genes Mla13, mlo, Mlf1, and Mli, and conversely no isolate was avirulent on the differential lines possessing the genes MlRu2, MlLa, Mlh, Mla8, Mla25, and Mlj. The frequencies of isolates overcoming the genes Mlg, Mla7, and Mla27 were 0 to 16% at individual locations; frequencies of isolates overcoming the genes Mla9, Mla17, and Mla18 ranged from 37 to 78%, and frequencies of virulences to genes Mla1, Mla3, Mla6, Mlp1, Mlat, Mla12, Mlra, Mlk1, Mla19, Mla20, Mla26, Mla28, Mla29, Mla30, Mla32, and mlt1 were 79 to 99%. Based on examination of 376 isolates collected in the same years from the Czech Republic, these populations differed greatly from the Israeli ones. The Czech populations showed greater diversity of virulence and lower mean virulence complexity than the Israeli populations. Diversity in the Israeli populations differed also among clusters of niches at the same location.
Keywords: f. sp.; barley powdery mildew